Angiotensin-converting enzyme genotypes and sarcoidosis: Correlation with susceptibility, progression and treatment response - Møller, Janne; Hilberg, Ole; Nissen, Peter Henrik; Møller, Holger Jon; Bendstrup, Karen Elisabeth (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Introduction: Previous research has yielded conflicting results regarding the association between ACE genotypes and both susceptibility to sarcoidosis and disease prognosis. While some studies have found no significant impact of the ACE genotype on sarcoidosis susceptibility, others have suggested that the DD genotype may be associated with an increased risk of developing the disease and a poor prognosis.This study aimed to evaluate the influence of ACE genotypes on the susceptibility to sarcoidosis, prognosis and treatment response in patients with pulmonary sarcoidosis in Denmark.Methods: Patients with sarcoidosis were consecutively enrolled and genotyped using allele-specific PCR and high-resolution melting methods. The distribution of ACE genotypes was then compared with that of 400 healthy Danish individuals. To assess the impact of ACE genotypes on sarcoidosis prognosis, their association with changes in pulmonary function tests, radiological staging over 24 months, the frequency of Löfgren’s syndrome, and treatment response were analyzed.Results: Among 148 patients with sarcoidosis, the frequency of the II, ID, and DD genotypes was 25%, 52%, and 23%, respectively. No significant difference was observed in the distribution of ACE genotypes between patients and controls. Prognostic factors and treatment response also did not vary among the genotypes. Conclusion: Our findings do not support an association between the ACE I/D genotypes and sarcoidosis susceptibility, prognosis or response to treatment in a Danish cohort.